A new species of Anthurium (Araceae) from Ecuador - Croat, Thomas B.; Ulloa Ulloa, Carmen; Freire, Efraín L. (Phytotaxa, 2015)
Anthurium sect. Belolonchium (Araceae) is defined and characterized.  One new species of sect. Belolonchium, namely A. yanacochense Croat, C.Ulloa & E.Freire from Pichincha province, Ecuador, is described as new and compared with related species.